Climate Policy under Technology Spillovers - Rolf Golombek; Michael Hoel (Fondazione Eni Enrico Mattei (FEEM), 2003)
Technological development is likely to play an important role in curbing growth in greenhouse gas emissions. It is therefore important to incorporate factors influencing technological change in climate policy analyses. This paper studies climate policy when there are technology spillovers between countries, and there is no instrument that (directly) corrects for these externalities. The lack of an appropriate instrument reflects that R&D expenditures in a country are difficult to verify by other countries. We show that without an international agreement, the non-cooperative outcome will have too much emissions and too little R&D expenditures compared with the social optimum. While the non-cooperative equilibrium depends on whether countries use tradable quotas or carbon taxes as their domestic instruments for controlling emissions, all countries are better off in the tax case than in the quota case. Next we study two types of international climate agreements with full participation. One is a Kyoto type of agreement where each country is assigned a specific number of internationally tradable quotas. In the second type of agreement a common carbon tax should be used domestically in all countries. We show that none of the cases satisfy the conditions for the social optimum. Even if the total number of quotas is set so that the quota price is equal to the Pigovian level, R&D investments will be lower than what is socially optimal in the Kyoto case, whereas with a harmonized domestic carbon tax R&D expenditures could even be too high. Finally we examine the case in which there is an incomplete agreement, i.e. some countries have not signed the agreement. We demonstrate that there is virtually no difference between this case and the case of full cooperation.
Keywords: O30; H23; Q20; Q28; Q48; 330; Climate policy; international environmental agreements; R&D; technology spillovers; Klimaschutz; Umweltabkommen; Forschung; Spillover-Effekt; Emissionshandel; Ökosteuer; Theorie